The Impact Of Corporate Governance Strategies On Banks Performance - Huda Layth Jawad Al-Sammak (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Effective corporate governance enhances bank performance and stability, yet Iraq’s banking sector continues to face challenges due to weak governance frameworks that constrain financial efficiency. This research looks at how Iraqi banks' profitability relates to corporate governance norms, particularly audit committees, board independence, and size. Return on assets (ROA) serves as the primary statistic in this research, which employs a quantitative, hypothesis driven methodology to examine the relationship between financial performance and governance parameters. The JASP software was used for both structural analysis and statistical evaluation of the data. The sample comprises 54 banks listed with the Central Bank of Iraq, based on the availability of their 2023 annual reports. Path coefficient, multiple, and panel regression analyses were used to assess the relationships among the variables. The findings indicate a positive and substantial correlation between board size and profitability. Although statistically negligible, the audit board has a negative link with profitability; yet, neither board independence nor the risk committee demonstrates a statistically meaningful impact on it. This research addresses a notable gap in the literature by focusing on Iraq's distinct governance landscape, offering valuable insights for investors, governments, and senior executives aiming to enhance governance standards.